Quorum Sensing in Bacterial Pathogenesis - Hossein Saghi; Fateme Moradi; Razieh Mohseni; Amir Hossein Abadi; Ramezan Ali Ataee; Parnia Baban Zadeh; Maryam Meskini; Davoud Esmaeili (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2015)
Introduction: Quorum sensing (QS) in the word means a gathering or a fixed number of objectives and say the microbes sense of awareness of the presence of bacteria and their community is. Bacteria in social life, the greatest benefit from the competitive environment to get the genetic regulatory mechanisms they use. Materials and Methods: This paper is a review article through library research and internet search sites, PubMed, Sid, Google Scholar keyword (Quorum sensing, AHL, pathogenesis) is collected in the years 2005 to 2014. Results: Quorum sensing in bacteria (pathogens and non-pathogens) regulates cell activity in quickly adapting to changing environmental conditions for maintenance and survival of bacteria in the environment. Process that is regulated by Quorum sensing including biofilm formation, Conjugation, produce virulence factors, toxin production and escape from the immune system. In this paper, we investigate the existence QS in gram-negative and gram-negative bacteria and its role in the pathogenesis of some of the major virulence factors are discussed. Conclusions: Increased prevalence of bacterial strains resistant to antimicrobial drugs is a big problem to find a new way to treat these infections is important. QS System to prevent damage to the opportunity to respond to the signal and prevent the bacteria express virulence factors follows. My hope is that by using antagonists and agonists can control so many dangerous diseases.